2021
DOI: 10.3126/jofa.v1i1.36249
|View full text |Cite
|
Sign up to set email alerts
|

Economic Diplomacy for Development Partnership

Abstract: The turn of events after the end of the Cold War called for revisiting traditional approaches to foreign policy. Shift in the world order triggered by enhanced economic activities in the national, regional and international markets has increased the need for coordinated economic diplomacy. Nepal, after the restoration of democracy in 1990, attempted to institutionalise and practise economic diplomacy through the Ministry of Foreign Affairs and its overseas missions. Exploring the leading features of economic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An economic diplomacy is a diplomatic approach that involves negotiation, cooperation, and setting economic relations between countries (Shrestha, 2021). Economic diplomacy promotes national economic interests, increases international trade, and facilitates cross-border investment (Okano-Heijmans & Asano, 2018).…”
Section: Of Economic Diplomacy Green Economic and Green Diplomacymentioning
confidence: 99%
See 1 more Smart Citation
“…An economic diplomacy is a diplomatic approach that involves negotiation, cooperation, and setting economic relations between countries (Shrestha, 2021). Economic diplomacy promotes national economic interests, increases international trade, and facilitates cross-border investment (Okano-Heijmans & Asano, 2018).…”
Section: Of Economic Diplomacy Green Economic and Green Diplomacymentioning
confidence: 99%
“…Economic diplomacy tends to focus on national economic and trade interests rather than adequately considering environmental aspects. This deficiency can lead to more attention to the negative environmental impacts arising from economic activities (Shrestha, 2021). On the other hand, a green economy (environment) focuses on sustainable and environmentally friendly economic growth.…”
Section: Of Economic Diplomacy Green Economic and Green Diplomacymentioning
confidence: 99%
“…However, the interconnections are crucial in pursuing what may be called total diplomacy. Shrestha (2021) remarked that it has potential for development and economic growth, which prospects for conducting coordinated economic diplomacy. The study identified that the main focus of economic diplomacy should be on trade promotion, investments, technology transfer and tourism.…”
Section: Introductionmentioning
confidence: 99%
“…. Previous, LDC graduates have faced similar challenges more specifically, Maldives, Cape Verde, and Samoa were successful to negotiate with the EU for further extension of the EU's Everything but Arms (EVA) trade preferences(Shrestha, 2021). Nepal must follow the path of other graduates and bilaterally approach this issue with…”
mentioning
confidence: 99%